Characteristics of patients discharged and readmitted after COVID-19 hospitalisation within a large integrated health system in the United States. Issue 10 (3rd October 2021) - Huang, Cheng-Wei; Desai, Prashant P.; Wei, Kenneth K.; Liu, In-Lu Amy; Lee, Janet S.; Nguyen, Huong Q.
Abstract: Background: Limited studies have explored post-discharge outcomes following Coronavirus Disease 2019 (COVID-19) hospitalisation. We sought to characterise patients discharged following a COVID-19 hospitalisation within a large integrated health system in the United States. Methods: We performed a retrospective study of 2180 COVID-19 patients discharged between 1 April 2020 and 31 July 2020. The primary endpoint was all-cause observation stay or inpatient readmission within 30 days from discharge. Bivariate and multivariable logistic regression analyses were performed to estimate the association between key socio-demographic and clinical characteristics with risk of 30-day readmission. Results: The 30-day readmission rate was 7.6% ( n = 166); 30-day mortality rate was 1% ( n = 19). Most readmissions were respiratory-related (58%) and occurred at a median time of 5 days post discharge. Adjusted models showed that prior hospitalisations (Odds Ratio = 2.37, [95% Confidence Interval: 1.60–3.51]) and chronic pulmonary disease (1.56 [1.08–2.26]), were significantly associated with 30-day readmission. Longer duration from diagnosis to index admission was borderline associated with lower odds of readmission (0.95 [0.91–1.00]). Conclusion: Readmission and mortality rates for COVID-19 following discharge are low. Most readmissions occur early and are due to respiratory causes and may reflect the prolonged acute disease course.